Ze srebrnego ekranu do literatury i radia. O sztuce (i słuchowisku) "Podróż na księżyc" Moniki Milewskiej = From the silver screen to literature and radio. About "Journey to the moon", a play (and radio play) by Monika Milewska - Zwolińska, Barbara (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article I discuss a contemporary play by Monika Milewska, an author associated with Gdansk. The play was translated into the language of the radio and aired in 2014; in 2015 it was presented and awarded at the Two Theatres Festival in Sopot. My aim in this essay is to analyze the methods used by the writer to reconstruct the literary and the sound history of the birth of silent film.
Keywords: Milewska, Monika (1972- ); Lumiere, Louis Jean (1864-1948); Mélies, Georges (1861-1938); "Journey to the Moon"; play; radio play; silent film; "Podróż na księżyc"; kino nieme; słuchowisko radiowe